POTENSI RELATIF SEKTOR PERTANIAN DALAM PEMBANGUNAN EKONOMI KABUPATEN BANGLI - Sugiari, Anak Agung Tri; Sudarma, I Made; Widhianthini, Widhianthini (JURNAL MANAJEMEN AGRIBISNIS; Vol 6 No 2 (2018): OKTOBER 2018DO - 10.24843/JMA.2018.v06.i02.p01, 2018)
The agricultural sector in Bangli Regency contributes the most to the Gross Regional Domestic Product (GRDP) of Bali Province which reaches Rp 939,394.0 million compared to other sectors. The large contribution of the agricultural sector is often not balanced with the growth of the region at the center of producing agricultural commodities themselves. Based on the Village Geographic Difficulties Index (IKG) released by Bali's Central Bureau of Statistics 2014, it noted that the highest IKG was in Bangli Regency. The high number of IKG in Bangli Regency can show that the potentials in Bangli Regency, especially the agricultural potentials have not been developed maximally. The purpose of this study is to explain the typology of Bangli Regency, explaining the potential and agricultural commodity in Bangli Regency, and also explaining the economic shift in Bangli Regency. This research was conducted in Bangli Regency using secondary data. Data analysis used is Klassen Typology analysis, LQ and DLQ analysis, and Shift Share analysis. The result of this research shows the typology of Bangli Regency are in quadrant IV (four), it means that the Bangli Regency is relatively in underdeveloped regions in Bali Province. The potential of agriculture commodities in Bangli Regency that need to be developed are crop commodities such as onion, cabbage, beans, squash, spinach, oranges, bananas, tobacco, and coffee plants. The result of Shift Share analysis shows that the economic structure in Bangli Regency is transformed from agriculture to service business field with the biggest total value of change then continued by industrial fields and the last field being agricultural business. Suggestions that can be made to the government of Bangli Regency are that they are expected to continue giving extension to the farmers, to prioritize the development and identify superior sectors, especially commodities that can be developed optimally in a certain area in, and maintain superior agricultural products which have been achieved at this time and spur the growth of developing commodities, so that superior products do not experience downward trend in the coming years. So, that Bangli Regency in the future can become a developed and fast growing region. In addition to the leading sectors, non-basic sectors, especially the agricultural sector should be paid more attention to in agricultural development planning; thus it is expected that Bangli Regency GRDP continues to increase.